1995
DOI: 10.1172/jci117737
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a mutant human fibrillin allele upon a normal human or murine genetic background recapitulates a Marfan cellular phenotype.

Abstract: The Marfan syndrome (MFS) is a connective tissue disorder inherited as an autosomal dominant trait and caused by mutations in the gene encoding fibrillin, a 350-kD glycoprotein that multimerizes to form extracellular microfibrils. It has been unclear whether disease results from a relative deficiency of wild-type fibrillin; from a dominant-negative effect, in which mutant fibrillin monomers disrupt the function of the wild-type protein encoded by the normal allele; or from a dynamic and variable interplay betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 27 publications
6
40
1
1
Order By: Relevance
“…It is important to avoid generalization of this observation to all mutant forms of fibrillin-1 in the absence of experimental validation. For example, multiple studies have demonstrated or implied that expression of isolated N-terminal peptides has the capacity to interfere with deposition of WT protein in cell culture systems (11,39). Given our present data and the availability of improved experimental reagents, it seems advisable to revisit this issue using animal models.…”
Section: Figurementioning
confidence: 95%
See 1 more Smart Citation
“…It is important to avoid generalization of this observation to all mutant forms of fibrillin-1 in the absence of experimental validation. For example, multiple studies have demonstrated or implied that expression of isolated N-terminal peptides has the capacity to interfere with deposition of WT protein in cell culture systems (11,39). Given our present data and the availability of improved experimental reagents, it seems advisable to revisit this issue using animal models.…”
Section: Figurementioning
confidence: 95%
“…Supportive evidence includes (a) autosomal dominant inheritance, (b) aggregation of fibrillin-1 molecules to form complex extracellular structures termed microfibrils (7), and (c) the dramatic paucity of extracellular microfibrils in patient-derived tissues, far less than the 50% level predicted from simple loss of contribution from the mutant allele (8)(9)(10). This deficiency could be recapitulated by either immunohistochemical or pulse-chase analysis of cultured dermal fibroblasts, suggesting that dominant-negative interference is not restricted to enhanced proteolytic clearance of mutant microfibrils over time, but rather could occur at the level of microfibrillar assembly (9,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…This results in disrupted microfibrillar architecture in the ECM. 12 Mutations in this gene result in classical MFS, neonatal MFS, autosomal dominant ascending aortic aneurysms, familial arachnodactyly, Shprintzen-Goldberg syndrome and severe progressive kyphoscoliosis, the 'MASS' phenotype (myopia, mitral valve prolapse, borderline aortic root enlargement, skin and skeletal findings), mitral valve prolapse syndrome, and autosomal dominant EL. There may be significant overlap between these conditions.…”
Section: Fbn1 and Marfan Syndromementioning
confidence: 99%
“…While experimental evidence and biosynthetic considerations had originally suggested that loss of tissue integrity is the underlying MFS pathogenesis (Hollister et al, 1990;Aoyama et al, 1994;Eldadah et al, 1995), clinical observations pointed to a larger role of fibrillin-rich microfibrils in organ physiology. Specifically, bone overgrowth, craniofacial features, valve and lung abnormalities, and muscle and fat hypoplasia argued for altered cellular behavior during morphogenesis Ramirez and Dietz, 2007).…”
Section: Mfs Pathophysiologymentioning
confidence: 99%
“…First described in 1896 by AntoineBernard Marfan (Marfan, 1896), MFS was later recognized by Victor McKusick as the founding member of the so-called heritable disorders of the connective tissue, which he predicted to be the result of structural or metabolic dysfunctions of ECM proteins (McKusick, 1955). Aside from confirming McKusick's prediction, the demonstration that fibrillin-1 mutations cause MFS provided a logical explanation for disease pathogenesis based on the concept that they would lead to the formation of a structurally impaired connective tissue by interfering with normal microfibril assembly (Aoyama et al, 1994;Eldadah et al, 1995).The recent creation of mouse models of MFS has questioned the original idea that MFS abnormalities are solely accounted for by loss of tissue integrity in that they have implicated perturbation of TGF-b signaling in the progression of the disease (Pereira et al, 1999;Bunton et al, 2001;Neptune et al, 2003;Ng et al, 2004). This paradigm switch has already paved the way for a new drug-based strategy that is based on TGF-b antagonism (Habashi et al, 2006).…”
mentioning
confidence: 99%